Case Series of Diabetic Ketoacidosis in Late Pregnancy with Normal Glucose Tolerance - Xu J; Liu C; Zhao W; Lou W (Dove Medical Press, 2023)
Jiwen Xu,1,* Chang Liu,1,2,* Weixiu Zhao,1 Weihua Lou1 1Department of Obstetrics and Gynecology, Renji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People's Republic of China; 2Center for Reproductive Medicine, Renji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Weixiu Zhao; Weihua Lou, Department of Obstetrics and Gynecology, Renji Hospital, School of Medicine, Shanghai Jiao Tong University, No. 160 Pujian Road, Shanghai, 200127, People's Republic of China, Email zhaowxiu12@163.com; louweihua@renji.comAbstract: Diabetic ketoacidosis (DKA) is rare in pregnancy, especially in pregnant women with normal glucose tolerance examined in early pregnancy. Once DKA occurs in pregnancy, the disease progresses rapidly and can be life-threatening for both mother and fetus. We concluded three cases of DKA in late pregnancy. The clinical manifestations, progression, and prognosis of the three cases are different, but all of the cases have normal glucose tolerance. We summarized the characteristics of pregnant women with DKA and analyzed and discussed them in conjunction with literature for reference by clinical doctors.Keywords: diabetic ketoacidosis, pregnancy, gestational diabetes mellitus